Neoadjuvant cemiplimab for resectable hepatocellular carcinoma: a single-arm, open-label, phase 2 trial. (March 2022) - Marron, Thomas U; Fiel, Maria Isabel; Hamon, Pauline; Fiaschi, Nathalie; Kim, Edward; Ward, Stephen C; Zhao, Zhen; Kim, Joel; Kennedy, Paul; Gunasekaran, Ganesh; Tabrizian, Parissa; Doroshow, Deborah; et al.
Summary: Background: Surgical resection of early stage hepatocellular carcinoma is standard clinical practice; however, most tumours recur despite surgery, and no perioperative intervention has shown a survival benefit. Neoadjuvant immunotherapy has induced pathological responses in multiple tumour types and might decrease the risk of postoperative recurrence in hepatocellular carcinoma. We aimed to evaluate the clinical activity of neoadjuvant cemiplimab (an anti-PD-1) in patients with resectable hepatocellular carcinoma. Methods: For this single-arm, open-label, phase 2 trial, patients with resectable hepatocellular carcinoma (stage Ib, II, and IIIb) were enrolled and received two cycles of neoadjuvant cemiplimab 350 mg intravenously every 3 weeks followed by surgical resection. Eligible patients were aged 18 years or older, had confirmed resectable hepatocellular carcinoma, an Eastern Cooperative Oncology Group performance status of 0 or 1, and adequate liver function. Patients were excluded if they had metastatic disease, if the surgery was not expected to be curative, if they had a known additional malignancy requiring active treatment, or if they required systemic steroid treatment or any other immunosuppressive therapy. After resection, patients received an additional eight cycles of cemiplimab 350 mg intravenously every 3 weeks in the adjuvant setting. The primary endpoint was significant tumour necrosis on pathological examination (defined as >70% necrosis of the resected tumour). Secondary endpoints included delay of surgery, the proportion of patients with an overall response, change in CD8 + T-cell density, and adverse events. Tumour necrosis and response were analysed in all patients who received at least one dose of cemiplimab and completed surgical resection; safety and other endpoints were analysed in the intention-to-treat population. Patients underwent pre-treatment biopsies and blood collection throughout treatment. This trial is registered with ClinicalTrials.gov (NCT03916627, Cohort B) and is ongoing. Findings: Between Aug 5, 2019, and Nov 25, 2020, 21 patients were enrolled. All patients received neoadjuvant cemiplimab, and 20 patients underwent successful resection. Of the 20 patients with resected tumours, four (20%) had significant tumour necrosis. Three (15%) of 20 patients had a partial response, and all other patients maintained stable disease. 20 (95%) patients had a treatment-emergent adverse event of any grade during the neoadjuvant treatment period. The most common adverse events of any grade were increased aspartate aminotransferase (in four patients), increased blood creatine phosphokinase (in three), constipation (in three), and fatigue (in three). Seven patients had grade 3 adverse events, including increased blood creatine phosphokinase (in two patients) and hypoalbuminaemia (in one). No grade 4 or 5 events were observed. One patient developed pneumonitis, which led to a delay in surgery by 2 weeks. Interpretation: This report is, to our knowledge, the largest clinical trial of a neoadjuvant anti-PD-1 monotherapy reported to date in hepatocellular carcinoma. The observed pathological responses to cemiplimab in this cohort support the design of larger trials to identify the optimal treatment duration and definitively establish the clinical benefit of preoperative PD-1 blockade in patients with hepatocellular carcinoma. Funding: Regeneron Pharmaceuticals